PENDIDIKAN KARAKTER DALAM NOVEL BINTANG KARYA TERE LIYE (KAJIAN SOSIOLOGI SASTRA) - Fitri Aghesty; Ahadi Sulissusiawan; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This research was motivated by interest to know the character education which is contained in Novel Bintang. The commons problem in this research is how is the character building in Novel Bintang? The sub problem is how is honest character education, the character of discipline, the character of hard work, independent character, intelligent character, curiosity character, the character of responsibility, character of caring for others, and character of caring for the environment? This study uses descriptive methods, in the form of qualitative. Sociology literature approach and documentary study techniques. The data collection tool is the researcher himself as a key instrument. The source of this research is Tere Liye. This study concludes that the concept of character education in Bintang novels includes some character education, namely: honest character (honestly admits mistakes and acknowledges ignorance). Character discipline (discipline to schedule). Hard working character (working hard in completing tasks). Independent character (independent in form does not depend on parents). Smart characters (intelligent logic, intelligent science, intelligent analyze, and smart to use the environment). Curiosity character (curiosity towards science). Character responsibility (responsibility for duty). Characters care about social (caring for others). Character caring for the environment (caring for the beauty of the environment).        Keywords: Character, Education, Novel.